Rehabilitasi Medik pada Pasien Coronavirus Disease 2019 - Parauba, Mercy C. K.; Gessal, Joudy; Lampah, Christopher (Medical Scope Journal, 2021)
Abstract: COVID-19 could cause respiratory, physical and psychological dysfunctions. These dysfunctions reduce the patient's functional capacity ultimately. Changes in physical function over a period of hospitalizations and critical illness are more common occurr in patients with more severe or pre-existing disease comorbidities which often lead to mobility disabilities and restrictions in activities of daily life. Physical medicine and medical rehabilitation play an impor-tant role in increasing the functional capacity of COVID-19 patients. This study was aimed to eva-luate the rehabilitation of COVID-19 patients. This was a literature review study using databases of Clinical Key, Web of Science, Pub Med, and Google Schoolar. The keywords used were rehabilitation COVID-19 OR rehabilitation SARS-CoV-2. Based on inclusion and exclusion criteria, eight literatures were selected. The result showed that early rehabilitation should be grant-ed to inpatients with COVID-19. Patients with restricted mobility due to quarantine or lockdown should receive exercise programs to reduce the risk of frailty, sarcopenia, cognitive decline, and depression. Telerehabilitation may represent the first option for individuals at home. In conclusion, proper rehabilitation can reduce the consequences of decreasing functional capacity.Keywords: rehabilitation; COVID-19 patientsÂ Abstrak; COVID-19 dapat menyebabkan disfungsi pernapasan, fisik, dan psikologis yang menurunkan kapasitas fungsional pasien. Perubahan fungsi fisik selama periode rawat inap dan penyakit kritis lebih umum dialami oleh pasien dengan penyakit COVID-19 yang lebih parah atau disertai komorbiditas dan dapat berakibat cacat mobilitas dan pembatasan dalam aktivitas kehi-dupan sehari-hari. Kedokteran fisik dan rehabilitasi medik memiliki peran penting dalam mening-katkan kapasitas fungsional pasien COVID-19. Penelitian ini bertujuan untuk mengetahui peran rehabilitasi medik pada pasien COVID-19. Jenis penelitian ialah literature review menggunakan database Clinical Key, Web of Science, PubMed, dan Google Scholar. Kata kunci yang digunakan yaitu rehabilitasi COVID-19 OR rehabilitasi SARS-CoV-2. Seleksi data berdasarkan kriteria inklusi dan ekslusi mendapatkan delapan literatur. Hasil penelitian menunjukkan bahwa rehabilitasi dini harus diberikan kepada pasien rawat inap dengan COVID-19. Pasien dengan mobilitas terbatas karena karantina atau lockdown harus menerima latihan program untuk mengurangi risiko kelemahan, sarkopenia, penurunan kognitif, dan depresi. Telerehabilitasi mungkin merupakan pilihan pertama bagi individu di rumah. Simpulan penelitian ini ialah rehabilitasi dini yang tepat dapat mengurangi konsekuensi penurunan kapasitas fungsional.Kata kunci: rehabilitasi; pasien COVID-19